LEGAL ANALYSIS ON THE LAW OF THE BOY BERNARDO AND ITS EFFECTIVENESS IN PRACTICAL APPLICATIONS - do Carmo, Mà´nica Bento; dos Santos, Dilma Faria Aniceto (CIPEEX, 2022)
THE MENINO BERNARDO LAW, LAW NO. 13.010, OF JUNE 26, 2014, WAS CREATED TO GUARANTEE CHILDREN AND ADOLESCENTS THE RIGHT TO BE RAISED AND EDUCATED WITHOUT THE USE OF PUNISHMENT (PHYSICAL PUNISHMENT AND/OR CRUEL OR DEGRADING TREATMENT). LAW NO. 13.010/2014 CAME TO MEET THE DEVICE ART. 227 OF THE FEDERAL CONSTITUTION WHERE IT IS EXPLICIT THAT IT IS THE DUTY OF THE FAMILY, SOCIETY AND THE STATE TO ENSURE WITH ABSOLUTE PRIORITY TO CHILDREN, ADOLESCENTS AND YOUNG PEOPLE SEVERAL RIGHTS, INCLUDING DIGNITY AND RESPECT (FEDERAL CONSTITUTION OF 1988). IN THIS SENSE, THIS PAPER AIMS TO UNDERSTAND WHAT IS BEING DONE TO MAKE THIS LAW EFFECTIVE AND WHAT PUBLIC POLICIES ARE BEING IMPLEMENTED TO ENSURE THESE RIGHTS. WITH THE CREATION OF THE MENINO BERNARDO LAW, THE NEED WAS FELT TO CREATE POLICIES TO TRAIN THE PROFESSIONALS WHO DIRECTLY ASSIST THIS PUBLIC TO PREVENT, IDENTIFY, AND COMBAT THESE FORMS OF VIOLENCE. THE FEDERAL GOVERNMENT HAS CREATED TRAINING PROGRAMS, ESPECIALLY FOR GUARDIANSHIP COUNSELORS WHO DEAL DIRECTLY WITH MOST OF THE CHILD AND ADOLESCENT VICTIMS OF ABUSE. BESIDES THESE ACTIONS, BRAZIL IS PART OF A GLOBAL PARTNERSHIP FOR THE END OF VIOLENCE AGAINST CHILDREN LED BY THE UN (WHERE THE GOAL IS TO CONTRIBUTE TO THE ELIMINATION OF ALL FORMS OF VIOLENCE AGAINST CHILDREN AND ADOLESCENTS). WHAT MEASURES ARE TAKEN FOR THOSE RESPONSIBLE WHO, INSTEAD OF CARING, EDUCATING AND PROTECTING THESE VULNERABLE MINORS, USE PHYSICAL PUNISHMENT, CRUEL OR DEGRADING TREATMENT? THEY WILL BE SUBJECT TO FAMILY PROTECTION PROGRAMS, PSYCHOLOGICAL OR PSYCHIATRIC TREATMENT, ORIENTATION PROGRAM COURSES, THE OBLIGATION TO REFER THE CHILD TO SPECIALIZED TREATMENT AND/OR A WARNING. IN PRACTICE, PERMANENT EDUCATIONAL CAMPAIGNS SHOULD BE PROMOTED, INVOLVING THE JUDICIARY, THE PUBLIC MINISTRY AND THE GUARDIANSHIP COUNCIL TO PROMOTE THE PROTECTION AND DEFENSE OF THE RIGHTS OF CHILDREN AND ADOLESCENTS. IT IS UNDENIABLE THAT THE CHILD BERNARDO LAW WAS A MILESTONE IN THE FIGHT AGAINST THE EXCESSES AND ABUSES THAT CULTURALLY ARE CARRIED OUT AS IF IT WERE NORMAL, BUT IT IS STILL ONLY THE BEGINNING OF THIS FIGHT. EVEN THOUGH THESE CHANGES HAVE BROUGHT COUNTLESS BENEFITS, WE STILL NEED TO CONTINUE FIGHTING AGAINST THE INEQUALITIES AND EVILS EXERCISED MAINLY BY THOSE WHO SHOULD PROTECT, WELCOME, AND GUIDE IN AN ADEQUATE MANNER.